Experience of Oesophageal atresia management in a tertiary Bangladeshi hospital - Islam, Md Kabirul (Acta Biomedica Atenei Parmensis, 2018)
Objectives: Background and aim: This study has been conducted to determine the clinical presentations and surgical outcome of patients with OA admitted in a tertiary level hospital in Bangladesh. Methods: A prospective analysis was conducted for 32 patients with confirmed OA between July 2007 and June 2015. Of them surgical correction was done in 25 cases. The other 7, in whom surgery could not be done, were excluded from the study. Results: Of the 25 cases, that had been operated, 15 were full term and 52% were more than 48 hours old. Type-C OA with TOF was the commonest type (96%). 24 cases were operated through Right Thoracotomy. Of them 52% were done by Single Lung (left) ventilation. ‘Division of the fistula’ with ‘end to end anastomosis’ was done in all of them. Only 1 patient had a Gastric pull up surgery. Of the 25 cases, 16 survived (64%). In follow up all the patients were found thriving and showed no problem in swallowing. Conclusion: Our study which shows 64% survival is a great achievement for us but not satisfactory in international standard. However, the experience and encouragement that we are gathering, will guide us to achieve better result in near future.